Warm red-ginger foot soaking for headache relief: A case study among hypertensive elderly - Andani, Nur; Rasdiyanah, Rasdiyanah; Djaha, Yohan Trayanus Lasarus (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Headache is a clinically relevant complaint among elderly people with hypertension, yet evidence regarding simple culturally familiar complementary nursing interventions such as warm red-ginger foot soaking remains limited. This study aimed to evaluate the effectiveness of warm red-ginger water foot-soaking therapy in reducing headache intensity among elderly patients with hypertension. A descriptive case-study design was conducted at Puskesmas Tamalanrea Jaya, Makassar City, involving two participants aged ≥60 years with physician-diagnosed hypertension and headache complaints. Data were collected through interviews, observation, questionnaires, and repeated pain assessment using the Verbal Descriptor Scale supported by the Numeric Rating Scale. The intervention consisted of soaking both feet in warm red-ginger water for 15–30 minutes over a 3–5-day period. Before the intervention, the first participant reported a pain score of 6, categorized as moderate pain, while the second participant reported a score of 7, categorized as severe pain. Following the intervention, pain scores decreased to 3 and 2, respectively, both categorized as mild pain. These findings suggest that warm red-ginger foot soaking may serve as a simple, accessible complementary nursing intervention to reduce headache complaints and improve comfort among elderly patients with hypertension. Further controlled studies with larger samples are required to confirm effectiveness and determine its broader clinical applicability.